Cost-per-responder analysis of patients with lenalidomide-refractory multiple myeloma receiving ciltacabtagene autoleucel in CARTITUDE-4 - Hansen, Doris K.; Lu, Xiaoxiao; Puglianini, Omar Castaneda; Sorensen, Sonja; Usmani, Saad Z.; Zhang, Eileen; Huo, Stephen; Zhang, Yan; Qureshi, Zaina P.; Jagannath, Sundar (Frontiers in Immunology, 2024)
Ciltacabtagene autoleucel (cilta-cel) is a chimeric antigen receptor T-cell therapy approved for patients with relapsed/refractory multiple myeloma (RRMM). In the phase 3 trial, CARTITUDE-4 (NCT04181827), cilta-cel demonstrated improved efficacy vs. standard of care (SOC; daratumumab plus pomalidomide and dexamethasone [DPd] or pomalidomide plus bortezomib and dexamethasone [PVd]) with a ≥ complete response (≥CR) rate of 73.1% vs. 21.8%. A cost-per-responder model was developed to assess the value of cilta-cel and SOC (87% DPd and 13% PVd) based on the CARTITUDE-4 trial data from a US mixed payer perspective (76.7% commercial, 23.3% Medicare). The model was developed using progression-free survival (PFS), overall survival (OS), and ≥CR endpoints from CARTITUDE-4 over a period of 25.4 months. Inpatient stays, outpatient visits, drug acquisition, administration, and monitoring costs were included. The base-case model assumed an inpatient setting for each cilta-cel infusion; another scenario included 30% outpatient and 70% inpatient infusions. Costs of managing grade 3-4 adverse events (AEs) and grade 1-4 cytokine release syndrome and neurotoxicity were included. Subsequent therapy costs were incurred after disease progression; terminal care costs were considered upon death events. Outcomes included total cost per treated patient, total cost per complete responder, and cost per month in PFS between cilta-cel and SOC. Costs were adjusted to 2024 US dollars. Total cost per treated patient, total cost per complete responder, and total cost per month in PFS were estimated at $704,641, $963,941, and $30,978 for cilta-cel, respectively, and $840,730, $3,856,559, and $42,520 for SOC over the 25.4-month period. Cost drivers included treatment acquisition costs before progression and subsequent treatment costs ($451,318 and $111,637 for cilta-cel; $529,795 and $265,167 for SOC). A scenario analysis in which 30% of patients received an outpatient infusion (assuming the same payer mix) showed a lower cost per complete responder for cilta-cel ($956,523) than those with an infusion in the inpatient setting exclusively. This analysis estimated that cost per treated patient, cost per complete responder, and cost per month in PFS for cilta-cel were remarkably lower than for DPd or PVd, highlighting the substantial clinical and economic benefit of cilta-cel for patients with RRMM.